1972
DOI: 10.1039/c39720000620
|View full text |Cite
|
Sign up to set email alerts
|

Chemical ionization mass spectrometry studies. Nitric oxide as a reagent gas

Abstract: Preliminary results indicate that it may be possible to identify the functional group present in many organic compounds from chemical ionization mass spectra recorded with nitric oxide as the reagent gas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…Hunt and Ryan have reported that the nitric oxide chemical ionization spectra of secondary alcohols show abundant (M -1)+, (M -17)+, and (M -2 + 30)+ ions. 17 It was proposed that the (M -2 + 30)+ ion is formed by oxidation of the alcohol and subsequent attachment of NO+ to the resulting ketone.17 However, reaction of NO4 with 1 and 2 yields ( + 30)+ ions and no (M -2 + 30)4…”
Section: + G+ -M-+ + Gmentioning
confidence: 99%
“…Hunt and Ryan have reported that the nitric oxide chemical ionization spectra of secondary alcohols show abundant (M -1)+, (M -17)+, and (M -2 + 30)+ ions. 17 It was proposed that the (M -2 + 30)+ ion is formed by oxidation of the alcohol and subsequent attachment of NO+ to the resulting ketone.17 However, reaction of NO4 with 1 and 2 yields ( + 30)+ ions and no (M -2 + 30)4…”
Section: + G+ -M-+ + Gmentioning
confidence: 99%
“…than on the formation of the acylium ions A and B. This conclusion is confirmed by a comparison of the CI (NO) spectra of methyl (Z)-octadec-9-enoate obtained (a) with a Kratos MS 25 RF (NO pressure in the ion source [8][9][10][11][12] The mechanism of formation of the acyl ions is still not obvious. So far, the following observations have been reported : (i) the elemental composition has been confirmed by exact mass measurements;' (ii) the acylium structure has been confirmed by identical collisional activation ( We now present further experimental data which may shed some additional light on this peculiar process.…”
Section: Rch-chr' + No+ + Rco+(a) And/or R'co+(b)mentioning
confidence: 76%
“…Reactions [6] and [7] are the lowest energy fragmentation routes (Fig. 3) while reactions [8] and [9], analogous to reactions [2] and [3] for C,H,,+, have been reported earlier (5) as higher energy fragmentation routes.…”
Section: Chemical Ionization Mass Spectra Of C6 Alkanolsmentioning
confidence: 99%
“…The exception to this trend is observed in the N,0/H2 CI spectra where, except for the tertiary alcohol, the (M -H)+ ion intensity is enhanced as a result of H-abstraction by NO+, present as one of the reactant ions. Hydride ion abstraction from alcohols by NO+ has been observed, as has the inability of NO+ to abstract H-from tertiary alcohols (7). It should be noted that a significant fraction of the C,H9+ ion signal may originate by H 2 0 loss from the (M -H)+ ion rather than by reaction [3].…”
mentioning
confidence: 99%